Whale shark Rhincodon typus strandings in the Gulf of California, Mexico. Issue 1 (7th December 2018) - Whitehead, Darren A.; Becerril‐García, Edgar E.; Petatán‐Ramírez, David; Vázquez‐Haikin, Abraham; González‐Armas, Rogelio; Galván‐Magaña, Felipe
Abstract : The present study analyses whale shark Rhincodon typus stranding in the Gulf of California, Mexico, reported by the public, scientists, authorities and artisanal fishermen. A total of 14 strandings were documented during the period 2001–2018. The total length of R. typus ranged from 350–1, 102 cm, with a sex ratio of 3.5:1 (males: females). This study highlights potential stranding areas, the need for better stranding protocols to assist R. typus recovery and the importance of samples from dead animals for scientific research.